Users’ Perception on Their Experience with FamPay - Rudresh Pandey; K.S. Rao; Rupali Chaurasiya; Nishant Upadhayay; Sairaj Hongekar; Ajay Massand; Sofea Zafiera binti Mohd Daud; Daisy Mui Hung Kee; Nurin Jasmin Binti Mohamed Nazir; Nurathirah Binti Mohamed Harun; Parvina A/P Sangelee Thevan (AIBPM Publisher, 2021)
The objective of this paper is to determine customer satisfaction with FamPay. Since marketing strategies are positively associated with customer satisfaction, organizations need to design customer-value driven marketing strategies to satisfy customer’s needs. Thus, several organizations, such as FamPay, have moved away from mass marketing and toward target marketing. The study used a quantitative method with questionnaires to collect data from respondents. The findings indicated that marketing strategies have impact on the customer satisfaction.